2018
DOI: 10.18632/oncotarget.25545
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and optimization of cardenolides inhibiting HSF1 activation in human colon HCT-116 cancer cells

Abstract: Combinational anticancer therapy demonstrates increased efficiency, as it targets different cell-survival mechanisms and allows the decrease of drug dosages that are often toxic to normal cells. Inhibitors of the heat shock response (HSR) are known to reduce the efficiency of proteostasis mechanisms in many cancerous cells, and therefore, may be employed as anti-tumor drug complements. However, the application of HSR inhibitors is limited by their cytotoxicity, and we suggested that milder inhibitors may be em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Our results revealed that pretreatment with BT44 reduced the resistance of colon carcinoma cells to etoposide ( Figure 3 ) and increased etoposide-induced apoptosis in U-937 cells with high levels of Hsp70 (U-937 wt HS and U-937 hsp70 ; Figure 4 B,C). Similar growth inhibition and pro-apoptotic effects have been demonstrated in HCT-116 cell lines following modulation of the activity of the HSF1 molecular chaperone [ 24 ].…”
Section: Discussionsupporting
confidence: 58%
“…Our results revealed that pretreatment with BT44 reduced the resistance of colon carcinoma cells to etoposide ( Figure 3 ) and increased etoposide-induced apoptosis in U-937 cells with high levels of Hsp70 (U-937 wt HS and U-937 hsp70 ; Figure 4 B,C). Similar growth inhibition and pro-apoptotic effects have been demonstrated in HCT-116 cell lines following modulation of the activity of the HSF1 molecular chaperone [ 24 ].…”
Section: Discussionsupporting
confidence: 58%
“…With respect to future clinical applications of a combined HSF-1 and Hsp90 inhibition to overcome radioresistance of tumor cells, presently different HSF-1 inhibiting substances such as quercetin [65], KNK437 [66], triptolide [67], NZ28 [29,31], N-amino-ethylamino derivative of colchicine (AEAC) [68], and cardenolide [69] are under investigations. However, effective concentrations in the micromolar range of quercetin, KNK437 and NZ28 are expected to exert adverse effects in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although not yet identified in gastric cancer, many HSF1 mediated inhibitors are being studied. Cantharidin [ 81 , 98 ] and Cardenolide CL-43 [ 99 ] have been shown to inhibit HSF1 transcriptional activity in cancer cells. In addition, PW3405 [ 100 ] and Compound 1 [ 101 ] were discovered as inhibitors of HSF1 by inhibition of phosphorylation.…”
Section: Hsf1 As a Biomarker In Gastric Cancermentioning
confidence: 99%